A review of the genus Kiwaia Philpott, 1930 (Lepidoptera, Gelechiidae) in the Palaearctic Region - Bidzilya, Oleksiy; Li, Houhun (Zootaxa, 2016)
Fourteen Kiwaia-species are recorded from the Palaearctic Region. Eight new species are described from China: Kiwaia (Empista) mengdana sp. n. (Qinghai), Kiwaia (Empista) nyingchiensis sp. n. (Xizang), Kiwaia (Empista) septentrionala sp. n. (Ningxia, Gansu, Shanxi and Sichuan), Kiwaia (Empista) centrica sp. n. (Gansu, Hunan), Kiwaia (Empista) montana sp. n. (Xizang), Kiwaia (Empista) medogia sp. n. (Xizang), Kiwaia (Empista) yadongensis sp. n. (Xizang) and Kiwaia (Empista) povolnyi sp. n. (Xizang). The hitherto unknown female of Kiwaia (Empista) kostjuki is described and this species is recorded from China for the first time. Gelechia dryosyrta Meyrick, 1931 from India is trasferred to Kiwaia: K. (Empista) dryosyrta (Meyrick, 1931) comb. n. Redescriptions and identification keys for all the Palaearctic species are provided, accompanied by illustrations of the adults, and male and female genitalia.